2021
DOI: 10.2147/cmar.s292293
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Features and Survival Outcome of 107 Newly Diagnosed Advanced Stage Extranodal NK/T-Cell Lymphoma Cases: A Triple-Center Study

Abstract: Objective Advanced stage extranodal natural killer/T-cell lymphoma (ENKTL) is a distinct type of non-Hodgkin lymphoma and the prognosis of ENKTL is poor with current treatment. This study aimed to investigate the clinical features, treatment strategy and survival outcome in patients with advanced stage ENKTL. Patients and Methods A total of 107 patients with newly diagnosed advanced stage ENKTL between January 2010 and December 2014 were reviewed from three cancer cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Survival outcomes in the large multicenter studies were similar to that of prospective phase 1/2 trials (3-year OS, 66-87.5%; 5-year OS, 60-82.1%) and retrospective studies (about 75%) in the early-stage ENKTCL [ 10 , 11 , 20 , 23 , 26 , 37 , 48 , 49 , 53 , 54 , 56 - 58 ]. Furthermore, the survival benefits of ASP/GEM-based regimens were prominent/substantial in advanced stage patients [ 9 , 18 , 37 ]. Consistent with the randomized controlled trial study [ 18 ], even compared with SMILE, one of the best-studied regimens, ASP/GEM-based regimens still resulted in superior outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Survival outcomes in the large multicenter studies were similar to that of prospective phase 1/2 trials (3-year OS, 66-87.5%; 5-year OS, 60-82.1%) and retrospective studies (about 75%) in the early-stage ENKTCL [ 10 , 11 , 20 , 23 , 26 , 37 , 48 , 49 , 53 , 54 , 56 - 58 ]. Furthermore, the survival benefits of ASP/GEM-based regimens were prominent/substantial in advanced stage patients [ 9 , 18 , 37 ]. Consistent with the randomized controlled trial study [ 18 ], even compared with SMILE, one of the best-studied regimens, ASP/GEM-based regimens still resulted in superior outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…According to the inclusion criteria, a total of 10 studies published between 2013 and 2022 were identified for the chemotherapy regimens review of ENKTCL [9,18,[35][36][37][38][39][40][41][42]. The article inclusion and exclusion procedures are demonstrated in a consort flow diagram of study selection (Fig.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 8 For advanced‐stage ENKTL, asparaginase‐containing chemotherapy is frequently administered, resulting in a 3‐year PFS rate of 49.2% and a 3‐year OS rate of 33%–49.4%. 9 , 10 Currently, there is no standard treatment strategy for PGINKTL, clinicians often refer to treatment for ENKTL, nasal type, and surgery for some patients; however, their value for treating PGINKTL remains unknown. Conversely, the survival outcomes of gastrointestinal NK/T‐cell lymphoma (GINKTL) seemed significantly worse than those of UAT‐ENKTL.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy combined with asparaginase‐containing chemotherapy is an established paradigm for early‐stage ENKTL treatment, resulting in 5‐year progression‐free survival (PFS) and overall survival (OS) rates of 64%–83% and 64%–89%, respectively 7,8 . For advanced‐stage ENKTL, asparaginase‐containing chemotherapy is frequently administered, resulting in a 3‐year PFS rate of 49.2% and a 3‐year OS rate of 33%–49.4% 9,10 . Currently, there is no standard treatment strategy for PGINKTL, clinicians often refer to treatment for ENKTL, nasal type, and surgery for some patients; however, their value for treating PGINKTL remains unknown.…”
Section: Introductionmentioning
confidence: 99%